Quality assessment, inclusive community development, and collective learning: An institutional perspective from Germany - Rohrmann, Albrecht; Schaedler, Johannes (Frontiers in Rehabilitation Sciences, 2022)
This article reviews the German discourse on quality of life, quality assurance and outcome measurement in services for persons with intellectual disabilities. Following institutional assumptions of path-dependencies in organizational development, it is argued that concepts such as quality assurance must be understood in the context of the national support system development. For the Federal Republic of Germany, it can be noted that previous approaches to quality assurance of services based on measurement and evaluation tools have not been the drivers of innovation for inclusion. The driving forces behind reforms in the disability field came from the three angles of the social service structure (people with disabilities, statutory welfare agencies, service providers). Policies of key actors were not part of a consistent reform strategy, however main elements of inclusive philosophies of the disability rights movement became hegemonial and led to national legislation that prioritizes person centered support arrangements in inclusive settings. With regard to governance arrangements in Germany and the idiosyncrasies of local disability fields it is suggested to conceptualize quality assurance in a multi-level approach as ‘local quality dialogues for collective learning’.